STUDENTS' INSIGHTS: EXPLORING THE IMPACT OF KAMPUNG INGGRIS LC TIKTOK ACCOUNT ON VOCABULARY ENHANCEMENT - Hafid Al Ghozali, Imam; Rizal, Daviq (Universitas Lambung Mangkurat, 2023)
Digital platforms such as TikTok have become increasingly popular in language learning in recent years, especially for students studying English as a foreign language (EFL). With regard to the platform's influence on EFL learners' language acquisition, the study addresses Kampung Inggris LC TikTok Account's novel approach to vocabulary building. The research aimed to explore EFL students' perspectives on using the Kampung Inggris LC TikTok Account as a tool for learning English vocabulary. The study used quantitative survey to gauge users' perceptions and experiences with Kampung Inggris LC TikTok Account. Out of the 126 participants in the study, 40 were students from UIN Walisongo and 86 were from Man 2 Tegal. Data collection was gathered through a Google Form. The findings of this study suggest that Kampung Inggris LC TikTok Account can be a valuable tool for EFL students to enhance their vocabulary skills. The videos' engaging and interactive nature make them appealing to a wide range of learners.